2013
DOI: 10.1177/2158244013498242
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Dissemination Interventions

Abstract: This literature review seeks to examine knowledge dissemination interventions (KDIs) implemented in health research and gauge their effectiveness on three kinds of outcomes: (a) knowledge acquisition, (b) changes in attitudes, and (c) changes in practice. MEDLINE and Cumulative Index to Nursing and Allied Health Literature databases from 2006 to 2011 were searched. Nineteen articles were retrieved. Most of the KDIs that were evaluated had a positive impact on knowledge acquisition and changes in attitudes, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 58 publications
(252 reference statements)
0
27
0
1
Order By: Relevance
“…The findings are organised according to the three outcomes for the measurement of effectiveness of KDIs: knowledge acquisition, changes in attitudes and changes in practices (Lafrenière et al 2013). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The findings are organised according to the three outcomes for the measurement of effectiveness of KDIs: knowledge acquisition, changes in attitudes and changes in practices (Lafrenière et al 2013). …”
Section: Resultsmentioning
confidence: 99%
“…In 2003 it was reported that only one in 10 of 175 applied research organisations in Canada evaluated KDIs for their effectiveness (Lavis et al 2006). In a systematic review by Lafrenière et al (2013), 11 of 19 KDIs that had been evaluated for effectiveness focused on the dissemination of results to health professionals, not to research participants, (Bhattacharyya et al 2011;Mitton et al 2007;Ward et al 2009) and generally showed changes in knowledge and attitudes but rarely in practices. Lafrenière et al (2013) identified a framework for evaluating the effectiveness of KDIs, focussing on knowledge acquisition, changes in attitudes and changes in practices.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations